The Remanufacturing of Track Rollers Requires The Application of A Hardfacing Technique, Which is Achieved by Combining Buttering with 309LMo Gas Metal Arc Welding (GMAW) and The TiC-O Flux-core Arc Welding (FCAW) Process - Addin Aristotika; Winarto Winarto; Sabandi Ismadi; Eddy Siradj; Muhammad Anis (MBI, 2025)
The operation of the track rollers is dependent on the frictional forces between the rollers and the track. Furthermore, the presence of moisture-laden sand and mud in the surrounding environment accelerates the corrosion process, leading to a synergistic effect on abrasion wear. The production of new rollers is a highly energy-intensive process, resulting in the emission of significant quantities of carbon dioxide. The main objective of this research was to develop a process for remanufacturing track rollers by integrating hardfacing methods, specifically, combining buttering with gas-metal-arc welding (GMAW) that utilizes 309LMo and flux-core arc welding (FCAW) employing TiC-O. During the GMAW process, currents of 180 A, 220 A, and 260 A were applied at the same time as wire with a diameter of 1.2 mm, whereas the FCAW process involved using currents of 200 A, 250 A, and 300 A in conjunction with a wire with a diameter of 1.6 mm. An evaluation was conducted through mechanical tests and metallurgical analysis to determine the effect of the variable current on the physical and mechanical properties of the hardfill layer. Mechanical tests using the Rockwell method and metallurgical analysis via morphological observation were conducted to assess the performance of the remanufactured track roller. The outcomes revealed that as the current increase in GMAW/FCAW welding, the hardfacing layer became increasingly stiffer, but this effect was offset by the failure of the hardfacing interface to bond correctly, as shown by its insufficient fusion and the formation of cracks and holes that penetrated into the base metal. This study highlights the importance of welding parameters to achieve a balance between hardness in the base and weld metals, diffusion, and the quality of the bond between the two, as a practical and cost-efficient method for the remanufacturing industry.